ISSUES OF ANTICORRUPTION POLICY REALIZATION IN TATARSTAN REPUBLIC AT MUNICIPAL LEVEL - S. F. Rakhimov (Russian Journal of Economics and Law)
The article analyzes the normative legal acts enacted in Tatarstan Republic and aimed at corruption prevention and counteraction. The author views the activity of the Republican Expert Group on corruption counteraction, and investigates the issues of state bodies and local self-government interaction with the civil society institutions in the sphere of corruption risks prevention. The author proposes certain measures for anti-corruption work organization at municipal level in order to increase the efficiency of corruption prevention and counteraction measures.